Greening the supply chain: an empirical study. Issue 1 (2nd January 2020) - Sajjad, Aymen; Eweje, Gabriel; Tappin, David
ABSTRACT: This article examines the notion of green supply chain management (GSCM) in the New Zealand business context. Despite the increasing significance of the GSCM approach at the global level, there is a paucity of empirical research that explores GSCM within the New Zealand business context. This study intends to bridge the gap in the literature by investigating the GSCM practices adopted by New Zealand based companies. To this end, a sample of 23 companies was selected and 29 interviews were conducted with senior corporate managers. The results revealed that most interviewees' companies were proactive in improving their mid-stream GSCM performance, but the same enthusiasm was not manifested at the upstream and downstream supply chain levels. Hence, we argue that companies need to recognise and embrace the holistic nature of GSCM and promote collaborative supply chain activities to realise improvements in environmental, economic and operational performance.